Keanekaragaman Jenis Mangrove Pada Tahura Ngurah Rai Sekitar PLTD/G Pesanggaran - Ni Luh Putu Mahendra Dewi; Shinta Enggar Maharani (Jurnal Ecocentrism, 2022)
Mangrove forest as a tropical coastal vegetation community is dominated by several species of mangrove trees that are able to grow and develop in muddy coastal tidal areas. This ecosystem has ecological and economic functions. Indonesia has the highest mangrove area, which is 3,112,989 ha or 22.6% of the world's total mangrove area. The majority of mangrove forests in Bali Province grow in the Ngurah Rai Taman Hutan Raya (TAHURA). This study aims to determine the condition and diversity of mangroves in The Ngurah Rai Tahura which borders the PLTD/G PT Indonesia Power UBPB Pesanggaran Denpasar. Types of Mangroves found in The Ngurah Rai Tahura Around PLTD/G Pesanggaran totaled 18 species, dominated by 6 species of mangrove with high importance (INP > 20%) respectively: Rhyzophora apiculata INP = 63.221%, Rhyzophora mucronata INP = 52.433%, Sonneratia alba INP = 30.323%, Sonneratia caseolaris INP = 28.670%, Xylocarpus granatum INP = 25.320 %, and Bruguiera gymnorrhyza INP = 22.421%. The results of the analysis of the Important Value Index as a whole are 298.342. This indicates that the mangrove community at the research site is quite stable, dense and stable, while the diversity index is 1.9546.